ANALYSIS OF THE FINANCING OF NON-FORMAL EDUCATION AND TRAINING IN THE REPUBLIC OF NORTH MACEDONIA - Dokmanovikj, Misho ; Spasevski, Darko; Shapkova Kocevska, Katerina; Gichevska, Sanja (Education for Employment in North Macedonia Project (E4E@мк), 2019)
This document presents the key findings and recommendations in relation to the financing of non-formal education and training in the Republic of North Macedonia that resulted from the empirical research conducted by the Institute for Strategic Research and Education – ISIE in the period December 2018 – March 2019, within the Education for Employment in North Macedonia Project (E4E@мк). The documentis consisted of research methodology (data collection, instruments, timeframe and structure of respondents); key trends in the development of non-formal education, as well as the results of the conducted research. The results refer to the verification process, organization of the non-formal education process, selection and structure of the training participants, cooperation with other institutions, monitoring of the quality, inclusiveness, as well as financing of non-formal education and training).